2019
DOI: 10.1016/j.heares.2019.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Gap-induced inhibition of the post-auricular muscle response in humans and guinea pigs

Abstract: A common method for measuring changes in temporal processing sensitivity in both humans and animals makes use of GaP-induced Inhibition of the Acoustic Startle (GPIAS). It is also the basis of a common method for detecting tinnitus in rodents. However, the link to tinnitus has not been properly established because GPIAS has not yet been used to objectively demonstrate tinnitus in humans. In guinea pigs, the Preyer (ear flick) myogenic reflex is an established method for measuring the acoustic startle for the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…The gap acts as a prepulse in reducing the startling response, but the same does not apply to animal tinnitus models [ 81 , 84 ]. It seems that tinnitus acts to fill the gap in the background noise, affecting the unconscious neural processing of GPIAS in the brainstem [ 85 ].…”
Section: Prepulse Inhibition As An Indicator Of Neural Plasticitymentioning
confidence: 99%
See 2 more Smart Citations
“…The gap acts as a prepulse in reducing the startling response, but the same does not apply to animal tinnitus models [ 81 , 84 ]. It seems that tinnitus acts to fill the gap in the background noise, affecting the unconscious neural processing of GPIAS in the brainstem [ 85 ].…”
Section: Prepulse Inhibition As An Indicator Of Neural Plasticitymentioning
confidence: 99%
“…There is no general consensus on the use of GPIAS in humans to assess tinnitus [ 85 ]. The studies carried out so far are discordant among themselves and also from animal studies [ 86 ].…”
Section: Prepulse Inhibition As An Indicator Of Neural Plasticitymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no peer-reviewed studies using reflexive measures in the chinchilla in response to acoustic stimuli (e.g., the startle response). It is possible that the paucity of startle studies in chinchillas is due to long release times from the startled state, or the presence of only subtle indicators of a startle response similar to those observed in the guinea-pig post-auricular response (Wilson et al , 2019).…”
Section: Chinchillas As a General Model For Hearing Sciencementioning
confidence: 99%
“…The use of the GPIAS paradigm for tinnitus assessment was originally based on the hypothesis that continuous tinnitus sound fills the silent gap and results in reduced inhibition of the gap response. Recent human studies have investigated the GPIAS paradigm, using eye blink or post-auricular muscle response as indicators of a startle response [12][13][14]. However, some animal studies reported results that contradict the "filling-in" hypothesis.…”
Section: Introductionmentioning
confidence: 99%